THE ROLE AND IMPORTANCE OF MODERNIZATION OF SERVICES IN ECONOMIC DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the importance and content of the modernization of services in the development of the economy. The data were compiled based on the authors' observations and analysis of foreign literature.